2020
DOI: 10.1002/pri.1851
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and activity after stroke. Secondary results from the Life After Stroke study

Abstract: Objectives: The aim of this study was to describe how the prevalence of fatigue changed from the subacute phase to the chronic phase after stroke, and to investigate how activity was associated with fatigue among participants included in the randomized controlled multicentre-study Life After STroke (LAST). Methods: The present study represents secondary analysis based on data from the LAST study. One-hundred-and-forty-five patients with mild and moderate stroke (mean (SD) age: 71.5 (10.5) years, 57.2% males) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Fatigue is a common experience in patients recovering from stroke. About 25%–85% of patients with stroke experience fatigue (Braaten et al, 2020; Michael & Macko, 2007). Chronic fatigue after stroke is a major concern; however, fatigue is subjective in nature and therefore requires input from those who are experiencing it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fatigue is a common experience in patients recovering from stroke. About 25%–85% of patients with stroke experience fatigue (Braaten et al, 2020; Michael & Macko, 2007). Chronic fatigue after stroke is a major concern; however, fatigue is subjective in nature and therefore requires input from those who are experiencing it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional measures (such as less time-consuming balance tests) may have led to more clinically feasible predictors. Factors known to be associated with PA such as motivation 46 or fatigue 56 were not examined in the LEAPS trial, nor were qualitative components such as outcomes expectations or social support. 57 In addition, daily steps was the only measure of PA, which does not encompass other forms of PA nor participant-reported PA. Our findings only apply to participants who adhered to wearing the activity monitor at both timepoints.…”
Section: Discussionmentioning
confidence: 99%
“…High interstudy heterogeneity was reported, with the rates tending to be low in the Asian countries that were surveyed [1]. Causes of post-stroke fatigue include anatomical and physiological changes such as stroke onset [5] as well as multiple other factors, including personality characteristics and physical factors [6,7], psychological factors [8], behavioral factors [9][10][11], and social factors [12,13]. In other words, occurrence of post-stroke fatigue involves multiple factors, the prevalence of which varies by country [1].…”
Section: Introductionmentioning
confidence: 99%